Enhanced Objectivity of AHP for More Reliable Solar Farm Site Selection - A. E. Dinçer; A. Demir; K. Yılmaz (Energy Science & Engineering)
ABSTRACT The analytic hierarchy process (AHP) is a popular decision‐making method for reliable decisions in different areas of study. Although the conventional AHP method mathematically ensures the consistency of results, the reliability of these results depends on the expert manifests. While AHP was originally proposed for subjectively relatable criteria, there may also be additional objectively relatable criteria or a consensus about the final relation of some couple of criteria. To address these objective relations and/or consensuses, this study proposes the analytic hierarchy process with optimized hierarchy (AHP‐OH). This method enhances the reliability of results by satisfying objective relations and/or consensuses about relations between criteria. The AHP‐OH methodology was applied to select optimal photovoltaic (PV) farm locations in Konya Province, Turkey, a region characterized by diverse terrain and solar radiation levels. The study incorporated geographic information systems to analyze criteria, such as solar radiation rate, land use, slope, proximity to roads and transmission lines, and restricted areas. Results demonstrated that 2.56% of Konya's terrain is highly (80%–100%) suitable and 19.34% of it has moderately high (60%–80%) suitability for PV farm development, with five highly suitable regions identified. Notably, the locations of existing PV farms aligned closely with the identified suitable zones, validating the efficacy of the AHP‐OH approach. This research underscores the importance of objectivity of decision‐making methods and proposes AHP‐OH to enhance the objectivity of the conventional AHP method. By providing a systematic and objective framework for spatial decision support systems, AHP‐OH offers significant advancements for policymakers and developers in the renewable energy sector. Future applications of this methodology can extend to other regions and renewable energy sources, contributing to global efforts in sustainable energy development.